Formulasi Indeks Kenyamanan Udara dalam Ruang pada Tempat Ibadah: Formulation of Indoor Air Comfort Index for Worship Buildings - Ramdani, Ahmad; Sabdo Yuwono, Arief (Departemen Teknik Sipil dan Lingkungan IPB, 2022)
Two main functions of public facilities are providing services to residents and maintaining environmental quality. There is currently no index that states the parameters of indoor air comfort quantitatively for worship buildings. The comfort for a building will affect the physical and mental health of its occupants. The research has identified and formulated an indoor air comfort index for worship buildings based on temperature, noise, odour, relative humidity, and light intensity that can be the best recommendations for district/city governments. The research has conducted using qualitative and quantitative methods. The qualitative method is based on filling the questionnaires by respondents and the quantitative method is based on the measurement of five parameters at the research site. The formulation obtained from the results of the weighting of the questionnaire and the index for each parameter. The indoor air comfort index is obtained based on five levels: uncomfortable, less comfortable, quite comfortable, comfortable, and extremely comfortable. The results of the research place of worship gave an index value of 4.0 at Tridharma temple that has declared comfortable, an index value of 2.9 at Church of Immanuel that have declared quite comfortable, and a range of index values of 3.1-3.8 at seven other sites that has declared comfortable.